HUBUNGAN ANTARA KESADARAN BERAGAMA DAN KEMATANGAN SOSIAL DENGAN AGRESIVITAS REMAJA (SANTRI) PONDOK PESANTREN MODERN ISLAM ASSALAAM SURAKARTA - Rama Furqona (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2009)
Adolescents—or we could call them the young generation—were a group whose very vulnerable to imitate aggressive behaviors such as fights, hostility, thievery, murder and other crimes. Santri—in this case—were also the same with other teenager from the same age group. The background of each santri before entering the dormitory in Islamic boarding school could cause a conflict between one santri with another when they interact with each other. This aggressive behavior could be much more damaging when santri tend to disobey religious norms and laws both while they are inside or outside of their school. Self consciousness in implementation of religions teaching in this case was seen as an important aspect that needs to be implanted by santri as a way of their life so they can realize and avoiding negative and inappropriate behavior in daily life. A deep understanding of social norms in the other hand must be taught to santri so they can adapt with their environment and society and furthermore they can defend themselves from any bad influence which would come to their life.This research concluded that there is a significance and correlation between religious self consciousness with Santri’s aggressive behavior as were written and published in many theories.